Importance of using basic statistics adequately in clinical research - Célio Fernando de Sousa Rodrigues (Brazilian Journal of Anesthesiology, 2017)
Background and objective: The inadequate use of basic statistics is the main responsible for scientific article misinterpretation. The purpose of this review article was to review some basic statistical topics to alert authors and readers about the importance of basic statistics proper reporting. Content: A bibliographical and cross-sectional study was carried out, which analyzed publications in books and articles in the following databases: SciELO (Scientific Electronic Library Online) and PubMed (Available from the National Center for Biotechnology Information). Medical research is not free from the risk of false positive and false negative results due to the choice of statistical tests and presence of small sample sizes. Conclusion: Understanding the correct use of basic statistics leads to fewer errors in reporting the results of studies performed and in the interpretation of their conclusions. Resumo: Justificativa e objetivo: O uso inadequado da estatística básica é o maior responsável pelo erro de interpretação dos artigos científicos. O objetivo deste artigo de revisão foi rever alguns tópicos básicos de estatística para alertar autores e leitores sobre a importância do relato adequado da estatística básica. Conteúdo: Foi feita pesquisa bibliográfica e transversal que analisou publicações em livros, artigos nas bases de dados SciELO (Scientific Electronic Library Online) e PubMed, do National Center for Biotechnology Information. Pesquisas na área médica não estão livres do risco de resultados falso positivos e falso negativos devido à escolha dos testes estatísticos e à presença de pequenos tamanhos de amostra. Conclusão: A compreensão acerca do uso adequado da estatística básica propicia menores erros nos relatos dos resultados de estudos executados e na interpretação das suas conclusões. Keywords: Biostatistics, Anesthesia, Sample size, Palavras-chave: Bioestatística, Anestesia, Tamanho da amostra